Detecting T-cell clonal expansions and quantifying clone survival using deep profiling of immune repertoires - Pavlova, Anastasia V.; Zvyagin, Ivan V.; Shugay, Mikhail (Frontiers in Immunology, 2024)
Individual's T-cell repertoire is constantly changing under the influence of external and internal factors. Cells that do not receive a stimulatory signal die, while cells that encounter and recognize a pathogen or receive co-stimulatory signal divide, resulting in clonal expansions. T cell clones can be traced by monitoring the presence of their unique T-cell receptor (TCR) sequence, assembled de novo via a process known as V(D)J rearrangement. Tracking T cells can give us valuable insights on cell survival after hematopoietic stem cell transplantation (HSCT), response to cancer treatment and indicate induction of protective immunity by vaccination. Here, we report a bioinformatic method for quantifying T-cell repertoire dynamics from TCR sequencing data. We demonstrate its utility by measuring T-cell repertoire stability in healthy donors, quantifying the effect of depleted lymphocyte infusion (DLI) and tracing the fate of different T-cell subsets in HSCT patients and tracking expansion of pathogen-specific clones in vaccinated individuals.